ETIKA KOMUNIKASI BISNIS DALAM PERSPEKTIF ISLAM : MEMBANGUN KEPERCAYAAN KONSUMEN MUSLIM DI ERA DIGITAL - Abdur Rohman Karim Amanulloh; Rifqi Fauzi Muttaqin (Gunung Djati Conference Series, 2025)
The evolution of digital technology has spawned a profound transformation in marketing strategies, especially in the realm of Islamic marketing. This article explains how innovations in digital marketing, when aligned with Shariah principles, can effectively resonate with Muslim consumers in the contemporary digital landscape. Using a descriptive qualitative methodology alongside literature analysis, the research underscores the importance of values such as honesty, transparency, and integrity in the formulation of ethical and religious-based marketing initiatives. The findings of the analysis show that the application of digital technologies, including social media and mobile apps, when executed in accordance with Islamic ethics, has the potential to increase engagement and loyalty among Muslim consumers. Moreover, important aspects such as halal certification, Islamic brand identity, and transparent and non-exploitative marketing communications are crucial in forging lasting relationships based on trust. This research is a major contribution to the corpus of Islamic marketing literature and provides practical insights for companies looking to navigate technological advancements while upholding the spiritual values of their consumer base.